(untitled) (Kronika Bydgoska, 2020)
World War II was the greatest armed conflict in the history of the world. The history of Poland during the German and Soviet occupation is usually presented from the perspective of the history of General Government. Another region encompassed lands incorporated to the Third Reich: Wielkopolska, Northern Mazovia, part of Silesia, and Pomerania. A quite different situation was related to the occupation period of Poland by the Soviets. This publication presents the less known history of Polish citizens from the areas annexed by the Third Reich and the USSR. The population of Pomerania, Silesia and Wielkopolska was captured and seized by the Third Reich. The Polish residents of Bydgoszcz had gone through hell, experiencing terror and humiliation from Nazi Germany. The Poles became victims of mass murders and deportations, were forcibly Germanized and conscripted to the Wehrmacht and other formations of the German Army. The history of the Poles who lived in the areas captured by the USSR included becoming a Soviet citizen and obligatory military service in the Red Army. These issues have not been explored in depth. The Poles in uniforms of foreign armies fell victim on all fronts of the war. These convoluted, frequently tragic stories require further research and should be subject to historical studies.